Environmental impacts of public transport systems using real-time control method. (March 2017) - Nesheli, Mahmood Mahmoodi; Ceder, Avishai (Avi); Ghavamirad, Farzan; Thacker, Scott
Highlights: Investigation and analyses of the benefits of using real-time PT operational tactics. Tactic-based control optimization model of holding, skip-stops, and boarding limit. Minimize total passenger travel time and maximize direct transfers. Environmental-related measure is the global warming potential. The model results in a 5.6% reduction in total global warming potential. Abstract: Public Transport (PT) systems rely more and more on online information extracted from both operator's intelligent equipment and user's smartphone applications. This allows for a better fit between supply and demand of the multimodal PT system, especially through the use of PT real-time control actions/tactics. In doing so there is also an opportunity to consider environmental-related issues to approach energy saving and reduced pollution. This study investigates and analyses the benefits of using real-time PT operational tactics in reducing the undesirable environmental impacts. A tactic-based control (TBC) optimization model is used to minimize total passenger travel time and maximize direct transfers (without waiting). The model consists of a control policy built upon a combination of three tactics: holding, skip-stops, and boarding limit. The environmental-related measure is the global warming potential (GWP) using the life cycle assessment technique. The methodology developed is applied to a real life case study in Auckland, New Zealand. Results show that TBC could reduce the GWP by means of reduction of total passenger travel times and vehicle travel cycle time. That is, the TBC model results in a 5.6% reduction in total GWP per day compared with an existing no-tactic scenario. This study supports the use of real-time control actions to maintain a reliable PT service, reducing greenhouse gas emissions and subsequently moving towards greener PT systems.